(untitled) (GEOmedia, 2022)
The preservation of historic buildings can often be particularly difficult due to the lack of detailed information about architectural features, construction details, etc. However, in recent years considerable technological innovation in the field of Architecture, Engineering, and Construction (AEC) has been achieved by the Building Information Modeling (BIM) process. In this case, it is more properly referred to as Historic - or Heritage - Building Information Modeling (HBIM). In the HBIM process, it is essential to precede the parametric modeling phase of the building with a detailed 3D survey that al-lows the acquisition of all geometric information. This methodology,called Scan-to-BIM, involves the use of 3D survey techniques to produce point clouds as a geometric “database” for parametric modeling. The “Real Cantina Borbonica" (Cellar of Royal House of Bourbon) in Partinico (Sicily, Italy) was chosen as a case study. The work has allowed achieving the HBIM of the "Real Cantina Borbonica" and testing an approach based exclusively on a topographic constraint to merge in the same reference system all the survey data (laser scan-ner and photogrammetric point clouds).